Identification of Leading Sectors of the Economy in Yogyakarta Using the Input-Output Method: Linkage Analysis of 17 Sectors by Business Field - Fadhillah, Muhammad Rifqi; Fausti Widayanti; Dian Wahyudi (Bulletin of Islamic Economics, 2025)
The Special Region of Yogyakarta (DIY) is one of the provinces in Indonesia whose economy is dominated by the Manufacturing Industry; Agriculture, Forestry, and Fisheries; Accommodation and Food Services; Information and Communication; and Construction. To determine the leading sectors, it is necessary to analyze linkage indices, as leading sectors are those with high dispersion indices, which are capable of driving economic activity. Therefore, this study uses the Input-Output analysis method to identify sectors with high linkage dispersion indices. The study utilizes the 2016 Yogyakarta Input-Output Table and analyzes the linkage values of potential sectors. Potential sectors are selected from 17 business fields out of a total of 52 industrial sectors. The analysis results show that the three sectors contributing the most output are Manufacturing Industry (Rp38,461 billion), Transportation and Warehousing (Rp30,615 billion), and Construction (Rp22,915 billion). The Transportation and Warehousing sector has the highest forward linkage of 1.822, indicating significant potential in driving the output of other sectors. On the other hand, the Public Administration, Defense, and Mandatory Social Security sector records the highest backward linkage of 1.602. The Manufacturing Industry sector has a backward linkage value of 1.515 and a forward linkage value of 1.750, while the Electricity and Gas Supply sector records respective values of 1.521 and 1.632. With high forward and backward linkage indices, these two latter sectors fall into the leading quadrant and have strong potential as the main drivers of DIY's economy.